Adenosine triphosphate-binding cassette member A3 gene mutation in children from one family from Saudi Arabia - Gawahir Mohamed Ahmed Mukhtar; Wadha Hilal Al Otaibi; Khalid Fahad Abdullah Al-Mobaireek; Suhail Al-Saleh (Annals of Thoracic Medicine, 2016)
Mutation in ABCA3, which is adenosine triphosphate-binding cassette member A3, a member of protein transporter family for phospholipids into the lamellar bodies during synthesis of surfactant, can cause lung disease related to surfactant dysfunction with autosomal recessive pattern. We reported three cases from same family with ABCA3 mutation, their gene, clinical course, and outcomes mentioning that one patient had successful lung transplantation, one started the process of the lung transplantation while the third one died during infancy. We concluded that the patients with ABCA3 gene mutations are increasing in numbers may be due to the availability of the genetic testing and high index of suspicion among physicians. Lung transplantation is the definitive treatment, but availability is limited in our region.